Protective effect of gallic acid against cisplatin-induced ototoxicity in rats - Kilic,Korhan (2019)
Abstract Introduction: Cisplatin is an antineoplastic agent widely used in the treatment of a variety of cancers. Ototoxicity is one of the main side-effects restricting the use of cisplatin. Objective: The purpose of this study was to investigate the protective efficacy of gallic acid, in biochemical, functional and histopathological terms, against ototoxicity induced by cisplatin. Methods: Twenty-eight female Sprague Dawley rats were included. Rats were randomly assigned into four groups of seven animals each. Cisplatin group received a single intraperitoneal dose of 15 mg/kg cisplatin. Gallic acid group received intraperitoneal gallic acid at 100 mg/kg for five consecutive days. Cisplatin + gallic acid group received intraperitoneal gallic acid at 100 mg/kg for five consecutive days and a single intraperitoneal dose of 15 mg/kg cisplatin at 3rd day. A control group received 1 mL intraperitoneal saline solution for five consecutive days. Prior to drug administration, all rats were exposed to the distortion product otoacoustic emissions test. The test was repeated on the 6th day of the study. All rats were then sacrificed; the cochleas were removed and set aside for biochemical and histopathological analyses. Results: In cisplatin group, Day 6 signal noise ratio values were significantly lower than those of the other groups. Also, malondialdehyde levels in cochlear tissues were significantly higher, superoxide dismutase and glutathione peroxidase activities were significantly lower compared to the control group. Histopathologic evaluation revealed erosion in the stria vascularis, degeneration and edema in the connective tissue layer in endothelial cells, impairment of outer hair cells and a decrease in the number of these calls. In the cisplatin + gallic acid group, this biochemical, histopathological and functional changes were reversed. Conclusion: In the light of our findings, we think that gallic acid may have played a protective role against cisplatin-induced ototoxicity in rats, as indicated by the distortion product otoacoustic emissions test results, biochemical findings and immunohistochemical analyses.